Emotional intelligence and its relationship to self-confidence among university students - Alqaisy, Lama Majed (Journal of Educational and Psychological Sciences, 2022)
The current study aimed to reveal the relationship between emotional intelligence and self-confidence among Tafila Technical University students, the study sample consisted of (500) male and female students, they were chosen randomly. The emotional intelligence and self-confidence scales were used to collect data. The results of the study indicated a high level of emotional intelligence among students, while the level of self-confidence was med, and there is a positive relationship between emotional intelligence and self-confidence, the results showed statistically significant differences (α = 0.05) in the emotional intelligence attributed to the sex in favor of females, and there were statistically significant differences (α = 0.05) on self-confidence in favor of males. The results indicated also that there were no statistically significant differences (α = 0.05) in the emotional intelligence attributed to the college, while there were statistically significant differences (α = 0.05) on the self-confidence scale attributed to the college variable in favor of human colleges. The study recommends paying attention to teaching positive psychology in various disciplines to achieve psychological and social adjustment for university students.
Keywords: emotional intelligence; self-confidence; university; students